Features of tire tread wear by rolling - Balaka, Maksym; Palamarchuk, Dmytro; Mishchuk, Dmytro (Кропивницький: Центральноукраїнський національний технічний університет, 2023)
Wear is a more complex process than external friction and is the result of the combined effect of physicochemical and mechanical processes that occur in the surface layer of the tire in contact with the supporting surface of the movement. The prevention task of premature wear and tear of tires is complex and involves the ability to determine their types, as well as unmistakably define the cause of each tire tear. Tire tread wear can occur by different mechanisms depending on the operation conditions: abrasive, fatigue, by rolling. At the same time, the total intensity of wear is determined by the ratio of individual types. Wear indices can change significantly when operating conditions change. Rolling wear is of particular interest, since this mechanism is realized for highly elastic materials and, in principle, cannot be observed in the friction of solid elements or solid rubbers. The wear mechanism by rolling is the highly intensive type. The pneumatic tire turns out to be short-lived if such a wear mechanism is realized.
Keywords: wear; tire tread; wear mechanism by rolling; operation conditions; intensity of wear; wheeled machine; rubber friction; 620.178.4